"It's just not easy to understand": Health insurance literacy and insurance plan decision-making among cancer survivors. Issue 28 (1st October 2022) - Williams, Courtney; Davidoff, Amy J.; De Moor, Janet; Vanderpool, Robin C.; Platter, Heather
Abstract : 16 Background: Little is known about how cancer survivors choose health insurance plans and whether low health insurance literacy (HIL) may lead to inadequate coverage or high out-of-pocket (OOP) costs. Methods: This prospective, explanatory mixed methods study assessed health insurance decision-making in a sample of adult cancer survivors < 5 years from diagnosis. Quantitative eye-tracking data were collected from two simulated health insurance plan choice sets to gauge interest in plan benefits (measured by dwell time, or seconds of no eye movement; longer dwell time indicates more interest). Ranking of the most important and confusing plan benefit, HIL (HIL Measure; scored 20-84, higher scores indicate higher HIL), and sociodemographic data were also captured. Differences in benefit-specific dwell time by HIL were estimated using adjusted linear models. Qualitative, semi-structured interviews clarified a subset of survivors' health insurance plan decision-making. Content analysis identified emergent patterns and themes. Results: With a median HIL score of 60 (IQR 50-70), survivors (N = 80) were 65% female, 59% non-Hispanic White, and a median age of 43 at diagnosis (IQR 34-52). Breast cancer diagnoses were most common (38%) and most survivors had received surgery (75%), radiation (55%), or systemic therapy (75%). In the choice set comparing a traditional and high-deductible health plan, survivors were most interested in prescription drug costs (median dwell time 58s, IQR 34-109), but no differences in interest were found comparing survivors with high and low HIL in adjusted models. In the choice set comparing a health maintenance organization and preferred provider organization plan, survivors were most interested in test and imaging costs (40s, IQR 14-67), with survivors with low vs. high HIL having more interest in deductible (β = 19s, 95% CI 2-38) and hospitalization costs (β = 14s, 95% CI 1-27) in adjusted models. Survivors with low vs. high HIL more often ranked low OOP maximums as the most important benefit (53% vs. 38%) and coinsurance as most confusing (68% vs. 53%). Interviews (n = 20) revealed survivors felt alone " to do their own research" about insurance choices. OOP maximums were cited as the deciding factor since it's "how much money is going to be taken out of my pocket." Coinsurance was referred to "rather than a benefit, it's a hindrance." Opinions about specialist gatekeeping were mixed; some survivors valued the accompanying lower OOP costs, while others worried about care delays. Survivors also reported issues with coverage and cost transparency post-insurance decision. Conclusions: Benefit considerations in health insurance decisions are varied and confusing for cancer survivors with both high and low HIL. Interventions to aid in health insurance understanding and choice are needed to optimize plan choice and prevent cancer-related financial hardship.